2020
DOI: 10.33393/grhta.2020.2138
|View full text |Cite
|
Sign up to set email alerts
|

Costo-utilità di dalbavancina versus standard of care (SoC) in pazienti con ABSSSI non severa in Italia

Abstract: Introduction: Acute Bacterial Skin and Skin Structure Infections (ABSSSIs) include all complicated skin and soft tissue infections. The aim of this study was to conduct a cost-utility analysis to compare dalbavancin with standard antibiotic therapies for the management of non-severe ABSSSIs from the National Health Service (NHS) perspective. Methods: A probabilistic decision tree model was developed considering a 30-days follow-up to simulate the therapeutic pathway of a patient treated with dalbavancin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In a previous study, a cost-utility analysis of dalbavancin for the management of non-severe ABSSSIs from the NHS perspective was conducted by comparing data regarding dalbavancin with the standard of care (SoC). For the study, a probabilistic decision tree model was developed considering a 30-days follow-up to simulate the therapeutic pathway of a patient treated with dalbavancin or SoC ( 17 ). The model considered three mutually exclusive health states: (a) discharge of patients from the emergency department, (b) discharge of patients after one night from admission, (c) discharge after 24 or 36 hours from admission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, a cost-utility analysis of dalbavancin for the management of non-severe ABSSSIs from the NHS perspective was conducted by comparing data regarding dalbavancin with the standard of care (SoC). For the study, a probabilistic decision tree model was developed considering a 30-days follow-up to simulate the therapeutic pathway of a patient treated with dalbavancin or SoC ( 17 ). The model considered three mutually exclusive health states: (a) discharge of patients from the emergency department, (b) discharge of patients after one night from admission, (c) discharge after 24 or 36 hours from admission.…”
Section: Introductionmentioning
confidence: 99%
“…In 99.7% of the simulations carried out, dalbavancin was dominant compared to the SoC. The analysis showed that dalbavancin may represent a cost-effective option compared to SoC for the treatment of patients with non-severe ABSSSI ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The promising efficacy in these challenging, off-label scenarios makes dalbavancin a viable alternative to daily intravenous or outpatient antimicrobial regimens. The simplified single or weekly administration regimen allows an early discharge, especially when adherence to oral therapy cannot be guaranteed or no oral choices are available ( 28 , 29 ).…”
mentioning
confidence: 99%